Modified spectrophotometric method for assay of angiotensin I-converting enzyme inhibitory activity of foodderived peptides - GAO Dan-dan; CAO Yu-sheng; MAI Xi (浙江大学学报. 农业与生命科学版)
A modified spectrophotometric assay was developed for determination of angiotensin Iconverting enzyme (ACE) inhibitory activity of peptides derived from plant protein, which was based on the classical paper chromatography determination of hippuric acid (HA) content in the urine. By using the modified method, the maximum absorbance of HA was measured at 459 nm, and the optimum chromogenic reaction conditions were as follows: temperature of 40 ℃, time for 30 min, and the DAB concentration of 0.5%. Captopril and cottonseed protein peptides showing antihypertensive activity as inhibitors of ACE were detected by this modified spectrophotometric assay. The result showed that the modified method was proved to be convenient, sensitive, accurate and reproducible, and it could be used for the screening of ACE inhibitory peptides derived from food proteins.